Women’s Self-Confidence in Education and Social Welfare: A Systematic Literature Review Based on International Women’s Day Insights - Bella Satiyo Putri; Raicha Oktafiani; Nadya Ulfha Sabila; Dominikus Djago Djoa (WISE Pendidikan Indonesia, 2025)
This study systematically reviews and synthesizes recent research on women’s self-confidence within the intersecting domains of education and social welfare, viewed through the normative and symbolic framework of International Women’s Day (IWD). Adopting a systematic literature review (SLR) design based on the PRISMA protocol, the analysis integrated evidence from 100 articles retrieved from Scopus, Web of Science, and Google Scholar between 2020 and 2024, of which 10 met the inclusion criteria after rigorous screening and quality appraisal. The findings reveal that women’s self-confidence functions as both a psychological resource and a social capital that bridges educational attainment, economic participation, and welfare engagement. Education consistently emerged as the most influential determinant of confidence, enhancing women’s decision-making capacity, autonomy, and leadership readiness, while social welfare systems acted as contextual enablers that transform confidence into tangible well-being. The synthesis further indicates that confidence mediates the relationship between educational empowerment and welfare realization, underscoring its dual role as both outcome and driver of gender equity. The discussion situates these findings within feminist social theory, self-efficacy, and capability frameworks, arguing that self-confidence is a relational construct shaped by institutional inclusion and socio-cultural norms. This review highlights the need for integrated educational welfare programs that incorporate psychosocial mentoring and policy support to sustain women’s empowerment. The implications of this study emphasize that fostering women’s self-confidence is not merely a matter of individual growth but a strategic and structural pathway toward inclusive social transformation and equitable development.